SPS234 : Sport facilities management / Faculty of Sport Science and Recreation - UiTM, Faculty of Sport Science and Recreation (Universiti Teknologi MARA (UiTM), 2025)
This course offers a foundation of the profession, including the defining characteristics of sport facility management and descriptions of the duties of a sport facility manager and the areas within the facilities. It also expose student to practical introduction to facility planning, design, management and maintenance. Also discussed are descriptions of the common indoor and outdoor elements of sports facilities, including sites selection, spaces, lighting, surfaces, utilities and storage areas.